Work-life balance of solo parent mothers during the COVID-19 pandemic - Liao, Samantha Therese SP (College of Home Economics, University of the Philippines Diliman, 2021)
This study aims to gain knowledge on the work-life balance of solo-parent mothers in the Philippines during the coronavirus disease (COVID-19) pandemic by looking into their work and home-life responsibilities and their perception of these. The participants of the study were 15 solo parent mothers who were selected through purposely and snowball sampling. The data was gathered through in-depth interviews and analyzed through thematic analysis. Results revealed that several of them experienced challenges such as managing finances, changes in work setup and childcare responsibilities, transition to online learning, and lack of self-care and leisure. Through support from their children and other adults, having multiple jobs, and time management, they were able to overcome these challenges. This also helped some of them become more productive in their work-life balance of the respondents depends on their perception of their responsibilities and their situation. Given the results, his study may shed light on the challenges faced by Filipino solo-parent families, and provide the public with knowledge that may be used to create programs to help empower solo-parent mothers.